DAMPAK PENGEMBANGAN BANDARA SUGIMANURU TERHADAP AKTIVITAS EKONOMI MASYARAKAT DI KECAMATAN KUSAMBI KABUPATEN MUNA BARAT (Studi Kasus Pada Sektor Informal Di Sekitar Bandara) - Ihsan Ihsan; Saemu Alwi; La Ode Samsul Barani (JEP (Jurnal Ekonomi Pembangunan), 2022)
This study aims to determine the impact of Sugimanuru Airport Development on Community Economic Activities in Kusambi District, West Muna Regency. Methods of data collection is done through observation, interviews, and documentation. The data analysis technique uses descriptive qualitative statistical techniques which provide a clear description of the research. The results of the research that have been obtained, it is known that the existence of Sugimanuru airport has an impact on the economy of the community in the area around the airport, both for the people of Kusambi District, especially for Kusambi and Guali villages. The majority of people admit that the existence of Sugi Manuru airport has an important role in improving the community's economy. Where people's income is seen, that there is a difference in people's income regarding income before the development and after the development of the Sugimanuru airport. This can also be seen from the impact of the existence of Sugi Manuru Airport.